Raters’ Assessment Quality in Measuring Teachers’ Competency in Classroom Assessment: Application of Many Facet Rasch Model - Mohamat, Rosyafinaz; Sumintono, Bambang; Abd Hamid, Harris Shah (Asian Journal of Assessment in Teaching and Learning, 2022)
This study examines the raters’ assessment quality when measuring teachers’ competency in Classroom Assessment (CA) using the Many Facet Rasch Model (MFRM) analysis. The instrument used consists of 56 items built based on 3 main constructs: knowledge in CA, skills in CA, and attitude towards CA. The research design of this study is a quantitative method with a multi-rater approach using a questionnaire distributed to the raters. Respondents are 68 raters consisting of The Head of Mathematics and Science Department, The Head of Mathematics Panel, and the Mathematics Teacher to assess 27 ratees. The ratees involved in this study are 27 secondary school Mathematics teachers from Selangor. The results show that among the advantages of MFRM are that it can determine the severity and consistency level of the raters, also detect bias interaction between rater and ratee. Although all raters were given the same instrument, the same aspects of evaluation, and scale category, MFRM can compare the severity level for each rater individually. Furthermore, MFRM can detect measurement biases and make it easier for researchers to communicate about the research findings. MFRM has the advantage of providing complete information and contributes the understanding of the consistency analysis of the rater’s judgement with quantitative evidence support. This indicates that MFRM is an alternative model suitable to overcome the limitations in Classical Test Theory (CTT) statistical models in terms of multi-rater analysis.